PENDIDIKAN, PELATIHAN DAN KINERJA PEGAWAI NEGERI SIPIL - Susi Artuti Erda Dewi (Universitas Riau, 2016)
Education, Training and Performance Civil Servants. This study aims to determine the effect of education and training on the performance of the Civil Service Agency for Community Empowerment, Government and Rural Development of Riau Province. This type of research is quantitative descriptive. The population is all Civil Servants in the Community Empowerment Board, Government and Rural Development Riau province that is numbered 91 people. All the population sampled. Data collection techniques were questionnaires, interviews, and observations. Analysis of data using multiple linear regression. The results showed that education and training each have a positive and significant impact on the performance of the Civil Service to the Community Empowerment Board, Government and Rural Development of Riau Province. While the constribution of education and training together has influenced the performance of 19.8%.